Balto models for memorial - Cole, Joseph E. (Cleveland Memory Project, 1925)
"Famous dog hero to be modeled for New York. Balto, the dog who brought serum and a blinded master into Nome, Alaska, in a raging blizzard, and whose efforts stopped the scourge of diptheria, is to be modeled in a panel relief by G. R. Roth, famous sculptor. The Municipal Art Society has appropriated $7,000 for the panel which will be placed in Central Park as a memorial. Photo shows Balto in the arms Gunnar Kasson, his driver and personal friend, giving the panel the dog "once-over,'' and Mrs. Roth.--photo verso.